PENGARUH LAMA EKUILIBRASI TERHADAP KUALITAS SEMEN BEKU BABI DUROC DALAM PENGENCER TRIS-MODIFIKASI DENGAN PENAMBAHAN KRIOPROTEKTAN (Effect of equilibration time on frozen sement quality of the duroc pig in tris diluents modification With..... - Biqshierz V.W Koelima; Henderiana L.L. Belli; Johny N. Kihe; Wilmientje M. Nalley (Universitas Nusa Cendana, 2022)
The purpose of this study was to test the influence of the equilibration time on the frozen semen quality of duroc pig in modified tris-egg yolk with the addition of extracellular cryoprotectants. Semen is collected twice per week using massage methods from two duroc males aged ±2.5 years which in good health and have been trained in semen colection. The design used is a completely randomized design with 4 tests and 3 treatments T1: equilibration time of 1 hour, T2: equilibration time of 2 hours, T3: equilibration time of 3 hours at a temperature of 50C. Observed parameters were motility, viability, abnormality, MPU, and recovery rate (RR). The results showed that motility, viability, abnormalities, MPU, and RR were higher (P<0.05) at 2 hours of equilibration (25.63±3.15%, 55.86±5.41%, 4.92±0.53%, 56.69±5.64%, 36.61±4.49%) compared to 1 and 3 hours (20.00±3.54%, 39.28±9.89%, 7.93±0.76%, 40.21±9.39%, 28.57±5.05%) and (15.00±4.08%, 32.19±7.0%, 8.41±0.70%, 32.71±7.07%, 21.43±5.83%). It was concluded the motility of duroc pig spermatozoa in the tris-modified diluents after 2 hours of equilibration reached 64.375% and 25.63% post thawing, but did not reach the requirement of 40% spermatozoa motility for artificial insemination. It was concluded that the sperm motility of Duroc pig in tris-modified diluent after 2 hours of equilibration reached 64.375% and 25.63% post thawing, but did not reach the standard of 40% spermatozoa motility for artificial insemination.